An optogalvanic gas sensor based on Rydberg excitations. (31st March 2020) - Schmidt, J; Münzenmaier, Y; Kaspar, P; Schalberger, P; Baur, H; Löw, R; Fruehauf, N; Pfau, T; Kübler, H
Abstract: We investigate the properties of a trace-gas sensing scheme based on Rydberg excitations at the example of an idealized model system. Rydberg states in thermal rubidium (Rb) are created using a 2-photon cw excitation. These Rydberg-excited atoms ionize via collisions with a background gas of nitrogen (N2 ). The emerging charges are then measured as an electric current, which is on the order of several picoampere. Due to the 2-photon excitation, this sensing method has a large intrinsic selectivity combined with a promising sensitivity of 10 ppb at an absolute concentration of 1 ppm. The determination of the detection limit is limited by the optical reference measurement but is at least 500 ppb.